Engineering of the spin on dopant process on silicon on insulator substrate. (20th October 2020) - Barri, Chiara; Mafakheri, Erfan; Fagiani, Luca; Tavani, Giulio; Barzaghi, Andrea; Chrastina, Daniel; Fedorov, Alexey; Frigerio, Jacopo; Lodari, Mario; Scotognella, Francesco; Arduca, Elisa; Abbarchi, Marco; et al.
Abstract: We report on a systematic analysis of phosphorus diffusion in silicon on insulator thin film via spin-on-dopant process (SOD). This method is used to provide an impurity source for semiconductor junction fabrication. The dopant is first spread into the substrate via SOD and then diffused by a rapid thermal annealing process. The dopant concentration and electron mobility were characterized at room and low temperature by four-probe and Hall bar electrical measurements. Time-of-flight-secondary ion mass spectroscopy was performed to estimate the diffusion profile of phosphorus for different annealing treatments. We find that a high phosphorous concentration (greater than 10 20 atoms cm −3 ) with a limited diffusion of other chemical species and allowing to tune the electrical properties via annealing at high temperature for short time. The ease of implementation of the process, the low cost of the technique, the possibility to dope selectively and the uniform doping manufactured with statistical process control show that the methodology applied is very promising as an alternative to the conventional doping methods for the implementation of optoelectronic devices.